Accountability ends, means and resources - Hayllar, Mark (1991)
This paper emphasises on the need to set up a system of accountability that will serve as the mechanism for evaluating the performance of government. It examines the ends, means and resources of accountability. It suggests the need to sort out the tools of accountability. It calls for the need for stocktaking in the system of accountability.
Keywords: Government accountability; Government liability; Administrative responsibility